Advanced building materials : selected, peer reviewed papers from the 2011 International conference on Civil Engineering, Architecture and Building Materials (CEABM2011), May 18-20, 2011, Haikou, China - International Conference on Civil Engineering, Architecture and Building Materials (2011 : Haikou, China); Li, Guangfan; Knovel (Firm) (Stafa-Zurich, Switzerland ; Enfield, N.H. : Trans Tech Publications)
Includes bibliographical references and index